Werner Herzog'un belgesellerinde hakikatin öznel bir bakışla yansıtılması - Kaplan, Burak (My University, 2025)
Werner Herzog'un belgesellerinde hakikatin öznel bir bakışla yansıtılması Bu tez, Werner Herzog’un belgesel sinema anlayışını Batı literatüründe süregelen kuramsal tartışmalar bağlamında ele almayı amaçlamaktadır. Son yıllarda dijital platformların yükselişi, belgesel filmlerin ulusal ve uluslararası festivallerdeki artan görünürlüğü ve televizyon yayıncılığındaki süreklilikle birlikte, belgesel üretiminde kayda değer bir artış yaşanmıştır. Bu niceliksel artış, beraberinde belgesel sinema üzerine yapılan akademik ve kuramsal çalışmaların da çoğalmasına zemin hazırlamıştır. Buna karşın, Batı akademik literatüründe belgesel sinema ile auteur (yönetmen odaklı) yaklaşımlar genellikle birbirinden ayrı ele alınmaktadır. Kendi sınıflandırmasına göre 39 belgesele imza atan Werner Herzog’un sinemasal mirası ise çoğunlukla kurmaca filmleri üzerinden değerlendirilmektedir. Bu çalışma, Herzog’un belgesel filmlerine odaklanarak, onun belgesel sinema içerisinde nasıl özgün bir pozisyon elde ettiğini incelemeyi amaçlar. Herzog’un “esrik hakikat” (ecstatic truth) kavramı, yalnızca estetik değil, aynı zamanda atletik (fiziksel), etik ve ontolojik bir yaklaşım olarak ele alınmakta; bu bağlamda gerçeklik ve temsil ilişkisine dair alternatif bir bakış sunmaktadır. Tez kapsamında Herzog’un belgeselleri, Bill Nichols’ın belgesel tipolojileri ile Stella Bruzzi’nin bu çerçeveye yönelik eleştirel katkıları doğrultusunda analiz edilmiştir. Ayrıca belgeselin, öznesine karşı taşıdığı etik sorumluluklar ve hakikat inşasındaki rolü sorgulanmıştır. Herzog’un olgu ile hakikat arasında kurduğu gerilim, hem çağdaş belgesel sinemanın temel tartışmalarına katkı sunmakta hem de günümüzde sıklıkla tartışılan “gerçeğe erişim” meselesine özgün bir öneri getirmektedir. Bu tez, belgesel sinemanın yalnızca belgeleyici değil, aynı zamanda düşünsel ve estetik düzlemde dünyaya dair bir söylem üretme biçimi olduğunu ileri sürmekte ve Herzog’un belgesel pratiği üzerinden bu savı teorik bir çerçeveye oturtmayı hedeflemektedir.

Subjective representation of truth in the documentaries of werner herzog This thesis explores Werner Herzog’s approach to documentary cinema within the framework of ongoing theoretical debates in Western academic literature. In recent years, the rise of digital platforms, the growing visibility of documentaries at both national and international film festivals, and their continued presence on television have contributed to a significant increase in documentary production. This quantitative expansion has also fostered a surge in scholarly and theoretical interest in the field. However, within Western film studies, documentary cinema and auteur-oriented approaches have typically been addressed in separate discourses. Despite directing nearly thirty documentaries, Werner Herzog’s cinematic legacy has largely been discussed through the lens of his fictional works. This study focuses on Herzog’s documentary practice and investigates the unique position he occupies within the tradition of documentary cinema. Central to this analysis is Herzog’s notion of “ecstatic truth,” a concept that offers not only an aesthetic vision but also an athletic (physical) ethical and ontological stance, proposing an alternative understanding of the relationship between reality and representation. Herzog’s documentaries are examined through the typologies of Bill Nichols and the critical perspectives of Stella Bruzzi, with a particular emphasis on the ethical responsibilities of the filmmaker toward their subject and the constructed nature of truth in documentary film. The tension Herzog constructs between fact and truth contributes to contemporary debates on the nature of reality and offers a distinctive philosophical response to the question of how truth can be represented. This thesis argues that documentary cinema is not merely a mode of recording but a form of esthetical and intellectual engagement with the world. Through an in-depth study of Herzog’s documentary oeuvre, the thesis aims to situate his work within a broader theoretical framework and contribute to current discussions in documentary film theory.
Subjective representation of truth in the documentaries of werner herzog
Keywords: Belgesel Film Kategorileri; Belgesel filmler; Belgesel Sinema; Documentary Cinema; Documentary Film Categories; Documentary films; Fact; Hakikat; Herzog, Werner, 1942-; Motion pictures; Olgu; Sinema; Truth; Werner Herzog; Werner Herzog Belgeselleri Werner Herzog; Werner Herzog Documentaries